1993
DOI: 10.1063/1.109706
|View full text |Cite
|
Sign up to set email alerts
|

Annealing of low-temperature GaAs studied using a variable energy positron beam

Abstract: Articles you may be interested inReduction of variable range hopping conduction in low-temperature molecular-beam epitaxy GaAs

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
15
0

Year Published

1993
1993
2013
2013

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(16 citation statements)
references
References 11 publications
1
15
0
Order By: Relevance
“…9,19 Positron annihilation results indicate the formation of defects larger than monovacancies during annealing. 10,11 It has been suggested that positron trapping in annealed LT-GaAs is related to As precipitates 20 whereas other authors interpreted their results in terms of isolated vacancy clusters. 10 The use of LT-GaAs for different applications requires a proper understanding of the defects which determine the properties of the material.…”
Section: Introductionmentioning
confidence: 77%
See 2 more Smart Citations
“…9,19 Positron annihilation results indicate the formation of defects larger than monovacancies during annealing. 10,11 It has been suggested that positron trapping in annealed LT-GaAs is related to As precipitates 20 whereas other authors interpreted their results in terms of isolated vacancy clusters. 10 The use of LT-GaAs for different applications requires a proper understanding of the defects which determine the properties of the material.…”
Section: Introductionmentioning
confidence: 77%
“…This is in accordance to the assumptions in the earlier PAS studies. [9][10][11]40,49 Due to the combination of different techniques in conjunction with theoretical calculations in the present study, the identification of V Ga can now be considered to be well established. Positron lifetime spectroscopy showed that the defects are monovacancies, whereas the conventional S -W analysis shows that they belong to the Ga sublattice.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…Thermal annealing experiments have been performed to elucidate vacancy formation mechanisms and the role of copper in determining the vacancy distribution in GaAs crystals (Elsayed et al, 2008(Elsayed et al, , 2011. LT-MBE GaAs is typically grown in conditions that favor the formation of Ga sublattice defects: Ga vacancies and As antisites (Bliss et al, 1992;Keeble et al, 1993;Störmer et al, 1996;Fleischer et al, 1997;Gebauer et al, 1997;Laine et al, 1999). The Ga vacancy-related defects follow the growth stoichiometry and compensate the n-type doping.…”
Section: Traditional Iii-v and Ii-vi Semiconductorsmentioning
confidence: 99%
“…Different authors used models based on arsenic clusters and different point-defects. PAS measurements show a significant increase in vacancy concentration upon annealing [23,24]. The anneal-induced defect formation occurs concurrently with increases in resistivity and lattice relaxation.…”
Section: Applicationsmentioning
confidence: 92%